Enhanced pyruvate dehydrogenase activity does not affect muscle O2 uptake at onset of intense exercise in humans - Bangsbo, Jens; Gibala, Martin J; Krustrup, Peter; Gonzalez-Alonso, Jose; Saltin, Bengt (American journal of physiology. Regulatory, integrative and comparative physiology, 2002)
Copenhagen Muscle Research Centre, Institute of Exercise and Sport Sciences, University of Copenhagen, Copenhagen, Denmark It has been proposed that the activation state of pyruvate dehydrogenase (PDH) may influence the rate of skeletal muscle O 2 uptake during the initial phase of exercise; however, this has not been directly tested in humans. To remedy this, we used dichloroacetate (DCA) infusion to increase the active form of PDH (PDH a ) and, subsequently, measured leg O 2 uptake and markers of anaerobic ATP provision during conditions of intense dynamic exercise, when the rate of muscle O 2 uptake would be very high. Six subjects performed brief bouts of one-legged knee-extensor exercise at ~110% of thigh peak O 2 uptake (65.3 ± 3.7 W) on several occasions: under noninfused control (Con) and DCA-supplemented conditions. Needle biopsy samples from the vastus lateralis muscle were obtained at rest and after 5 s, 15 s, and 3 min of exercise during both experimental conditions. In addition, thigh blood flow and femoral arteriovenous differences for O 2 and lactate were measured repeatedly during the 3-min work bouts (Con and DCA) to calculate thigh O 2 uptake and lactate release. After DCA administration, PDH a was four- to eightfold higher ( P  < 0.05) than Con at rest, and PDH a remained ~130% and 100% higher ( P  < 0.05) after 5 and 15 s of exercise, respectively. There was no difference between trials after 3 min. Despite the marked difference in PDH a between trials at rest and during the initial phase of exercise, thigh O 2 uptake was the same. In addition, muscle phosphocreatine utilization and lactate production were similar after 5 s, 15 s, and 3 min of exercise in DCA and Con. The present findings demonstrate that increasing PDH a does not alter muscle O 2 uptake and anaerobic ATP provision during the initial phase of intense dynamic knee-extensor exercise in humans. blood flow; lactate; creatine phosphate; dichloroacetate